Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1108/14684520610706406
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation into factors influencing the adoption of an e‐learning system

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
200
5
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(274 citation statements)
references
References 49 publications
21
200
5
12
Order By: Relevance
“…They have direct positive effects on the intention and motivation to use e-learning technologies -findings commensurate with those of prior research (Lee, 2006;Roca and Gagné, 2008).…”
Section: Conclusion and Implications For Practicesupporting
confidence: 70%
“…They have direct positive effects on the intention and motivation to use e-learning technologies -findings commensurate with those of prior research (Lee, 2006;Roca and Gagné, 2008).…”
Section: Conclusion and Implications For Practicesupporting
confidence: 70%
“…If a company enforces employees undertaking mandatory e-learning, extrinsic motivation tends to be muted or attenuated. Lee (2006) found that in order to increase the overall adoption of an e-learning system by students, mandatory use is necessary.…”
Section: Gender Differences In Learners' Attitudementioning
confidence: 99%
“…Some studies have opined that TAM can be extended in the quest to further investigate user"s behaviour. This has led to TAM being extended by some studies (Chau and Hu, 2001;Lee, 2006). These studies using the concept of TAM have confirmed that the perception of the user on ease of use and usefulness of technology are necessary determinants in the adoption of technology (Hashim, 2008;Purnomo and Lee, 2013).…”
Section: Technology Acceptance Modelmentioning
confidence: 95%